PERSEPSI MASYARAKAT TERHADAP BAITUL MAAL WAT TAMWIL (BMT) DALAM PEMBERDAYAAN EKONOMI MASYARAKAT - Solikhul Hidayat (Universitas Negeri Surabaya, 2018)
BMT is a financial institution that is engaged on a micro level, based on operations on economic principles lawful, fair and profitable. The role of Baitul Tamwil (productive economy) is as Baitul Maal (social roles) that serves to distribute capital surplus to the needy. The purpose of this study was to determine the extent of the public's perception of the existence of BMT in economic empowerment in Jepara. This study resulted in a recommendation that BMT is able to improve the performance and quality of the local economy. BMT institutionally is capable of providing a positive perception for people who use the services of BMT. This study is a descriptive study conducted. Descriptive method is a method in researching the status of groups of people, objects, state of thinking in the present system. The goal is to make the description or painting in a systematic, timely and reliable information on the facts, investigated the relationship between phenomena and to test hypotheses, make predictions, get the meaning and implications of a problem to be solved.